The Unifying Force of True Religion - Eradi, Balakrishna (Journal of Dharma, 1983)
I deem it a great privilege to have been invited to inaugurate this conference which has as its theme, "Role of Religion in National Integration" It is also appropriate and very gratifying that a discussion on this very important topic, which is of vital concern for the welfare of mankind and the preservation of man's culture and spiritual heritage, has been arranged on this occasion.